Surface functionalized magnetic nanoparticles for separation of beta-blocker Propranolol from aqueous solution (Journal of Chemical Engineering, 2014)
The present study investigates adsorption separation of beta-blocker (?-blocker), propranolol utilizing surface functionalized magnetic nanoparticles (MNPs) from phosphate buffer solution. Surface of MNP is functionalized with silica and carboxymethyl-?-cyclodextrin (CMCD) to scrutinize sorption removal characteristics. Modified MNPs are characterized by Fourier Transform Infrared (FTIR) Spectroscopy, Transmission Electron Microscopy (TEM) etc. Adsorption of propranolol onto magnetic nanoadsorbents is found to be dependent on solution pH and adsorption capacity of adsorbent increases as pH increases from 3 to 9 and then reaches plateau at pH 11. It appears that modified hydrophobicity of beta-blocker, propranolol affects interaction with cyclodextrin functionalized magnetic nanoparticles as well as adsorption capacity of the pollutant. Equilibrium data in aqueous solution is well represented by Freundlich isotherm model. XPS analysis reveals that propranolol adsorption on magnetic nanoparticles involves nitrogen atoms in side chain of propranolol to form surface complexes. Finally, desorption studies are carried out in different concentration of methanol solution and 50% methanol solution was found to be effective for almost complete desorption. DOI: http://dx.doi.org/10.3329/jce.v28i1.18104 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 14-21